Platelet endothelial aggregation receptor-1: a novel modifier of neoangiogenesis. (8th July 2015) - Vandenbriele, Christophe; Kauskot, Alexandre; Vandersmissen, Ine; Criel, Maarten; Geenens, Rachel; Craps, Sander; Luttun, Aernout; Janssens, Stefan; Hoylaerts, Marc F.; Verhamme, Peter
Abstract: Aims: Platelet endothelial aggregation receptor-1 (PEAR1) is a cell membrane protein, expressed on platelets and endothelial cells (ECs). PEAR1 sustains αIIbβ3 activation in aggregating platelets and attenuates megakaryopoiesis via controlling the degree of Akt phosphorylation. Its role in EC biology is unknown. The aim of this study was to determine the expression of PEAR1 in the human endothelium of various tissues and to investigate its role in ECs in vitro and in angiogenesis, using Pear1 −/− mice. Methods and results: PEAR1 is present on the membrane and on filo- and lamellipodia of human cultured ECs, and its expression coincides with CD31 in various tissues. PEAR1 expression is variable in ECs of different origin. Lentiviral knockdown of PEAR1 in cultured ECs doubled EC proliferation and significantly stimulated EC migration, in turn enhancing in vitro tube formation on matrigel through the Akt/PTEN-dependent p21/CDC2 pathway. Even when physiological blood vessel formation was unaffected in Pear1 −/− mice, neoangiogenesis in these mice was significantly increased both in a hind limb ischaemia ligation model [4.7-fold increase in capillary density in the ligated limb of Pear1 −/− mice compared with ligated limbs in wild-type (WT) mice] and in a skin wound-healing model, resulting in a two-fold faster wound closure in Pear1 −/− mice compared with WT littermates. Conclusion: We established an inverse correlation between endothelial PEAR1 expression and vascular assembly both in vitro and in vivo . These findings identify PEAR1 as a novel modifier of neoangiogenesis.